Evidence of Continuous Destruction of Historical Architectural Monuments of Artsakh by the Republic of Azerbaijan - Sarumyan, Nune (History and Culture, 2025)
The article attempts to highlight the policy of distortion and destruction of the historical fate of many Armenian churches, monasteries, libraries, museums and other historical and architectural monuments, pursued by the Armenian-hating authorities of Azerbaijan in the Armenian Artsakh world.It seems that the Azerbaijani authorities not only destroyed traces of Armenian culture, but also tried to whitewash everything that was Armenian.The continuation of expropriation by the Republic of Azerbaijan of historical and architectural monuments of Artsakh is revealed, its main goal is clarified - the elimination of the Armenians of Artsakh.
Keywords: Artsakh; expropriation; historical and architectural monuments; church; monastery complex; Armenian historical cemetery; archaeological monument; Yerevan Gate; distortion of facts; appropriation of cultural heritage